A Mycobacterium ulcerans Toxin, Mycolactone, Causes Apoptosis in Guinea Pig Ulcers and Tissue Culture Cells - George, Kathleen M. (American Society for Microbiology, 2000)
Mycobacterium ulcerans is the causative agent of Buruli ulcer, a tropical ulcerative skin disease. One of the most intriguing aspects of this disease is the presence of extensive tissue damage in the absence of an acute inflammatory response. We recently purified and characterized a macrolide toxin, mycolactone, from M. ulcerans. Injection of this molecule into guinea pig skin reproduced cell death and lack of acute inflammatory response similar to that seen following the injection of viable bacteria. We also showed that mycolactone causes a cytopathic effect on mouse fibroblast L929 cells that is characterized by cytoskeletal rearrangements and growth arrest within 48 h. However, these results could not account for the extensive cell death which occurs in Buruli ulcer. The results presented here demonstrate that L929 and J774 mouse macrophage cells die via apoptosis after 3 to 5 days of exposure to mycolactone. Treatment of cells with a pan-caspase inhibitor can inhibit mycolactone-induced apoptosis. We demonstrate that injection of mycolactone into guinea pig skin results in cell death via apoptosis and that the extent of apoptosis increases as the lesion progresses. These results may help to explain why tissue damage in Buruli ulcer is not accompanied by an acute inflammatory response.